The public perception toward the efficiency, sustainability and satisfaction of Kampung Tanpa Wayar 1 Malaysia in Putatan / Mohammad Raimi Ramlan and Samsir Aras - Ramlan, Mohammad Raimi; Aras, Samsir (2014)
The program of Kampung Tanpa Wayar 1 Malaysia (KTW1M) is a government program to develop the communication and technology of Malaysia especially in rural area. This program is under the project of Malaysian Communication and Multimedia Communication. The development of this program must be done continuously by the government in order to make sure the program is success and achieve its objectives. There are 3 variables can affect the public perception towards the efficiencies, sustainability and satisfaction of KTW1M which is to identify the public perception towards the efficiency of the KTW1M, investigate the perception of public towards the sustainability program of KTW1M and to study the level of public satisfaction of this program. The main objective of this study in overall is to find out the Public Perception toward the Efficiency, Sustainability and Satisfaction of Kampung Tanpa Wayar 1 Malaysia in Putatan.